Role of oral and maxillofacial surgeon in disaster management - Anggraini Santi; Nismal Harfindo; Akmal Fauzan; Rizqina Nurul; Apipi Muzaffar (E3S Web of Conferences)
This comprehensive review explores the role of oral surgery in disaster management, highlighting its various phases of disaster response. The study uses a qualitative literature review to analyze current practices, challenges, and future directions in integrating oral surgical expertise into disaster preparedness and response frameworks. Findings reveal that oral surgeons contribute significantly to patient care in disaster scenarios. Integrating oral surgery in disaster management remains inconsistent globally, including oral surgeons in response teams. It identifies inadequate specialized training, limited awareness among disaster planning authorities, and logistical difficulties in deploying oral surgical resources. Technological advancements offer promising solutions to enhance the reach and effectiveness of oral surgical care in disaster settings. It underscores the psychological impact of oral and maxillofacial injuries on disaster survivors, emphasizing the importance of timely interventions for mental health and social reintegration. Ethical considerations surrounding resource allocation in disaster scenarios are examined. The review concludes by proposing recommendations for policy development, training enhancement, interdisciplinary collaboration, and technology adoption to improve oral surgery in disaster management. This research contributes to a growing body of evidence supporting the essential role of oral surgery in comprehensive disaster response strategies and advocates for its fuller incorporation into global disaster management frameworks.